The effects of a mindfulness training intervention on fatigue and job satisfaction among emergency nurses: A quasi-experimental study - Alaa Jawad Kadhim; Naderh Mohammadi; Zahra Hezbiyan; Mohammad Abasinia; Reza Norouzadeh; Mohsen Taghadosi; Bahman Aghaie (Kashan University of Medical Sciences, 2024)
Background: Fatigue is a challenging problem for nurses working in the emergency department and makes them dissatisfied with their jobs.Objectives: This study examined the effects of a mindfulness training intervention on fatigue and job satisfaction in emergency nurses.Methods: A quasi-experimental study was conducted with 80 emergency department nurses in 2022. Participants were randomly assigned into an intervention group (n=40) and a control group (n=40). The intervention group received eight mindfulness training sessions, while the control group received no intervention. Data was collected using the Minnesota Satisfaction Questionnaire and the Multidimensional Fatigue Inventory a few days before the start and immediately after the end of the intervention. Descriptive statistics, t-test, paired t-test, and analysis of covariance (ANCOVA) were used to analyze the data.Results: The two groups did not differ significantly in their pretest fatigue mean scores. However, all posttest fatigue mean scores decreased in the intervention group, and the between-group differences were statistically significant (P < 0.05). The two groups also did not differ significantly in their pretest scores for internal, external, and general job satisfaction (P> 0.05). However, all posttest job satisfaction mean scores increased in the intervention group, and the between-group differences were statistically significant (P < 0.05). The ANCOVA showed that the nurses' pretest scores had no significant effect on the posttest scores for fatigue and job satisfaction.Conclusion: This study supports the potential benefits of the mindfulness intervention in overcoming fatigue and improving job satisfaction of nurses working in emergency department. Nurses are recommended to learn and implement mindfulness-based interventions to reduce their fatigue and improve their job satisfaction.